2007
DOI: 10.1021/jp0673314
|View full text |Cite
|
Sign up to set email alerts
|

On the Perturbation of the Intramolecular H-Bond in Diols by Supercritical CO2:  A Theoretical and Spectroscopic Study

Abstract: The role played by supercritical carbon dioxide used as a dispersant medium in the synthesis of polyurethane particles has been investigated. High-temperature-high-pressure in situ infrared spectroscopic measurements combined with ab initio calculations were performed to investigate the hydroxyl stretching vibrations of ethylene glycol (EG) and 1,4-butanediol (BD), two monomers commonly used in the field of step growth polymerization. Specific interactions between the diols and CO2 have been put in evidence. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Generally, CO 2 is considered a Lewis acid. It has been shown that CO 2 can interact with surfaces of oxides such as TiO 2 and CeO 2 as a Lewis acid through the carbon atom and bind to a surface oxygen atom, but bond formation is also possible between the oxygen atoms and Lewis acid surface sites possibly because CO 2 exhibits also weak Lewis base properties [46][47][48][49][50][51]. Note that scCO 2 as the solvent is present in large excess and hence, also a weak basicity could contribute significantly to the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, CO 2 is considered a Lewis acid. It has been shown that CO 2 can interact with surfaces of oxides such as TiO 2 and CeO 2 as a Lewis acid through the carbon atom and bind to a surface oxygen atom, but bond formation is also possible between the oxygen atoms and Lewis acid surface sites possibly because CO 2 exhibits also weak Lewis base properties [46][47][48][49][50][51]. Note that scCO 2 as the solvent is present in large excess and hence, also a weak basicity could contribute significantly to the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Here we elucidate the effect of the gold particle size of titania and ceria-supported gold catalysts used in the aerobic oxidation of benzyl alcohol at atmospheric pressure in conventional solvents as well as at high pressure in supercritical CO 2 which can act as a (weak) Lewis base [46][47][48][49][50][51]. The almost gas-like diffusion coefficients of solutes in dense carbon dioxide and the avoidance of phase boundaries under single-phase conditions in combination with its ability to solvate nonpolar gases as well as many organic compounds render it a promising reaction medium [52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…[19,33,34,[37][38][39][40] During recent years, quantum mechanical studies on the interaction between CO 2 and amines were mainly targeted to the study of supercritical CO 2 as an alternative to toxic organic solvents in industrial applications [41,42] and, in particular, as a dispersion medium in the synthesis of polymeric materials, such as polyurethane. [42,43] Studies have been also performed on the interaction between CO 2 and polymers. [13,41] Only recently, some works concerning the interaction between CO 2 and MOFs have appeared.…”
Section: Introductionmentioning
confidence: 99%
“…Relative energies of conformers (PBE1PBE/6-311þG(d,p)) and chemical shifts of OH protons (PBE1PBE/cc-pVTZ//PBE1PBE/ 6-311þG(d,p)) of propan-1,2-diol, 1-Me, in benzene at 298 K Conf. IR, [7,8,24,30,32,42,[84][85][86] Raman, [3] microwave [4,31] , and NMR [6,14,27,87] spectroscopies, and other less common experimental techniques, [29,40,42,88] but none gives direct evidence for hydrogen bonding, only for the proximity of hydrogen and oxygen on different OH groups. Theoretical calculations of various degrees of sophistication (molecular dynamics and Monte Carlo calculations, [2,[9][10][11]81,89] molecular mechanics [19,90] and semi-empirical [19,20] and ab initio [1,5,8,9,12,13,[15][16][17][18]21,25,28,30,33,[35][36]…”
Section: Cooperativity and Intramolecular Hydrogen Bondingmentioning
confidence: 99%